PENERAPAN METODE ROLE PLAYING PADA PELAJARAN IPAS DALAM MENINGKATKAN INTERAKSI SOSIAL SISWA KELAS V MADRASAH IBTIDAIYAH MA’HAD AL-ZAYTUN - Iqlima Firdaus; Dewi Utami; Moh. Mas’ud Arifin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Basic education plays an important role in the formation of character, knowledge, and social skills of students. However, the learning of Natural and Social Sciences (IPAS) is often still conventional through lecture methods, making students passive in learning and less interactive with each other. This study aims to describe the applications of the Role Playing method in IPAS learning and to determine its impact on improving social interactions of fifth grade grade stundents of Madrasah Ibtidaiyah Ma’had Al-Zaytun. This study uses a descriptive qualitative approach with data collection techniques through observation , interviews, and documentation. Data analysis is carried out interactively through reduction, data presentation and drawing conclusions with triangulation of technical sources and time to ensure the validity of the data. The result of the study indicate that the application of the Role Playing method has strategic steps that are u seful for creating a fun learning process and are able to create an active and collaborative learning atmosphere. Student become more courageous in expressing opinions, working together, and showing empathy and social responsibility. The positive impact of the applications of the Role Playing method is seen in the establishment of cooperation, assimilation, accommodation and acculturation. Meanwhile on the other hand, negative impacts can be seen from the emergence of controversional competition and conflicts that do not lead to violence. This fosters social dynamics that color differences and learning to respect each other.